Morals and villas in Seneca's Letters : places to dwell - Henderson, John, 1948- (Cambridge University Press, 2004)
John Henderson explores three letters of Seneca describing visits to Roman villas, and surveys the whole collection to show how these villas work as designs for contrasting lives. Seneca brings the philosophical epistle to Latin literature, creating models for moralizing which feature self-criticism, parody, and animated revision of myth.